Development of water-soluble 3, 5-dinitrophenyl tetrazole and oxadiazole antitubercular agents. Issue 20 (15th October 2017) - Roh, Jaroslav; Karabanovich, Galina; Vlčková, Hana; Carazo, Alejandro; Němeček, Jan; Sychra, Pavel; Valášková, Lenka; Pavliš, Oto; Stolaříková, Jiřina; Klimešová, Věra; Vávrová, Kateřina; Pávek, Petr; et al.
Graphical abstract: Abstract: In this work, four series of tertiary amine-containing derivatives of 3, 5-dinitrophenyl tetrazole and oxadiazole antitubercular agents were prepared, and their in vitro antimycobacterial effects were evaluated. We found that the studied compounds showed lipophilicity-dependent antimycobacterial activity. The N -benzylpiperazine derivatives, which had the highest lipophilicity among all of the series, showed the highest in vitro antimycobacterial activities against Mycobacterium tuberculosis CNCTC My 331/88 (H37 Rv), comparable to those of the first-line drugs isoniazid and rifampicin. The presence of two tertiary amines in these N -benzylpiperazine derivatives enabled us to prepare water-soluble dihydrochloride salts, overcoming the serious drawback of previously described 3, 5-dinitrophenyl tetrazole and oxadiazole lead compounds. The water-soluble 3, 5-dinitrophenyl tetrazole and oxadiazole antitubercular agents described in this work are good candidates for further in vitro and in vivo pharmacokinetic and pharmacodynamic studies.